2004
DOI: 10.1364/ao.43.005143
|View full text |Cite
|
Sign up to set email alerts
|

Design of a nonnull interferometer for aspheric wave fronts

Abstract: The presence of highly aspheric wave fronts in an interferometer leads to a need for system calibration, and this calibration requirement affects the design of the interferometer. Dynamic range, vignetting, and the ability to characterize components all must be considered during the design stages. The interferometer must be designed with respect to wave-front propagation as opposed to reference sphere aberrations. A nonnull interferometer for measurement of aspheric transmitted wave fronts has been developed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…There have been several papers which discuss calibration issues in non-null interferometry. 1,[3][4][5][6][7] The penalty for breaking the null condition is that errors introduced by the interferometer no longer cancel, since the reference and test wavefronts do not travel the same path through the interferometer. This causes part specific errors to be introduced into the measured wavefront.…”
Section: Calibrationmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several papers which discuss calibration issues in non-null interferometry. 1,[3][4][5][6][7] The penalty for breaking the null condition is that errors introduced by the interferometer no longer cancel, since the reference and test wavefronts do not travel the same path through the interferometer. This causes part specific errors to be introduced into the measured wavefront.…”
Section: Calibrationmentioning
confidence: 99%
“…It has been shown that these errors can be removed using reverse raytracing and reverse optimization. 1,[4][5][6][7] The need for calibration places several constraints on the design of a non-null system. In order to accurately predict and remove the aberrations introduced by the system, including the test part, the interferometer components must be accurately characterized.…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid this issue, most interferometry is used in a null configuration [2]. Null optics can compensate for a large aberration of a test optic such that the absolute value of the wavefront difference between any two adjacent pixels is less than half a wave, which is the well-known Nyquist condition [3]. The main disadvantage of using null optics is that a particular null optic has to be designed for the specific test optic, which increases the cost of the system and the production time.…”
Section: Introductionmentioning
confidence: 99%
“…The main disadvantage of using null optics is that a particular null optic has to be designed for the specific test optic, which increases the cost of the system and the production time. In order to overcome these limitations, Sub-Nyquist interferometry (SNI) was developed [3][4][5]. As a phase-shifting approach, SNI achieves a high dynamic range by recovering the phase information from the subsampled interferogram (by a sparse sensor) assuming the wavefront or surface slope is continuous.…”
Section: Introductionmentioning
confidence: 99%